Green SME Business Model in Bangka Belitung: A Value Chain Analysis Approach - Reniati, Reniati; Faisal, Faisal (AIBPM Publisher, 2023)
The objective of this research is to conduct a framework and business model study for Green SMEs by (1) identifying the definition, criteria, and indicators of Green SMEs based on the conditions in Bangka Belitung through a literature review and (2) developing and analyzing the Green SME business model by mapping Green SMEs under the supervision of the Customs and Excise Office of Type Madya Pabean C Pangkalpinang. The research methodology employed in this study is qualitative descriptive analysis, incorporating a literature review, presentation of field findings through tabulated data and descriptive information, and arguments based on previous research exploration. Subsequently, a Value Chain Analysis was conducted to map each primary activity and support the activity process. The results of the Green mapping indicate the following: there are ten respondents at the eco-traditional stage of Green SMEs, six respondents at the eco-adapters stage, three respondents at the eco-entrepreneur stage, and two respondents at the eco-innovators stage. Based on the existing Green practices in the Bangka Belitung Islands Province, critical points in Green practices were identified according to ideal Green indicators.